Rare heteromorphism in chromosome 9. About a case - Vidal-Hernández, Belkis del Carmen (2023)
Morphological variations of chromosome 9 constitute the second most common heteromorphism in humans, and can be observed in 6-8% of the general population. Carrier individuals have a history of reproductive disorders, infertility, and spontaneous abortions. The objective of this research was to present a case of a rare heteromorphism in chromosome 9, detected in the "Paquito González Cueto" Pediatric University Hospital located in the city of Cienfuegos, Cuba. A couple came to the center from the infertility consultation due to the existence of recurrent spontaneous abortions, for which a cytogenetic postnatal diagnosis is proposed. The result of the woman was normal and a rare finding was found in the husband's chromosome 9, which was corroborated as: 46, xy; der (9) inv.dup (9) (p11q13). It is concluded that it was an unusual heteromorphism, 2 polymorphic findings in the same chromosome with duplication and inversion of heterochromatin never before found in the literature. The presence of these rare variants in the same chromosome can cause spontaneous abortions in the couple.